2013
DOI: 10.1152/physiolgenomics.00002.2013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of Wistar-Kyoto rat and spontaneously hypertensive rat substrains from different sources

Abstract: Zhang-James Y, Middleton FA, Faraone SV. Genetic architecture of Wistar-Kyoto rat and spontaneously hypertensive rat substrains from different sources. Physiol Genomics 45: 528 -538, 2013. First published May 14, 2013 doi:10.1152/physiolgenomics.00002.2013.-The spontaneously hypertensive rat (SHR) has been widely used as a model for studies of hypertension and attention deficit/hyperactivity disorder. The inbred Wistar-Kyoto (WKY) rat, derived from the same ancestral outbred Wistar rat as the SHR, are normote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 36 publications
0
39
1
Order By: Relevance
“…In a recent animal model of depression, nicotine administration exacerbated depressive-like behavior in inbred Wistar-Kyoto (WKY) rats, which had reduced hippocampal volume but not in the control Wistar rats with comparatively large hippocampal volume (Tizabi et al, 2010). Research has also shown greater genotypic variability among WKY rats compared to other inbred strains Zhang-James et al, 2013). It has been proposed that the differential responses of WKY and Wistar rats to nicotine may reflect genetic differences (Tizabi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent animal model of depression, nicotine administration exacerbated depressive-like behavior in inbred Wistar-Kyoto (WKY) rats, which had reduced hippocampal volume but not in the control Wistar rats with comparatively large hippocampal volume (Tizabi et al, 2010). Research has also shown greater genotypic variability among WKY rats compared to other inbred strains Zhang-James et al, 2013). It has been proposed that the differential responses of WKY and Wistar rats to nicotine may reflect genetic differences (Tizabi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, WKY from Charles River/GER, a model for the predominantly inattentive subtype of ADHD (Sagvolden, Dasbanerjee et al 2008), have a large number (35%) of discordant SNP genotypes relative to WKY from Harlan/UK, a well-recognized control for SHR (Sagvolden, Johansen et al 2009). In contrast, WKY from Charles River/US have a small number (2.5%) of discordant SNP genotypes relative to WKY from Harlan/UK (Zhang-James, Middleton et al 2013), and are not expected to differ from WKY from Harlan/UK. Thus, WKY from Charles River/US were used as the inbred control herein.…”
Section: Introductionmentioning
confidence: 95%
“…In contrast, even other lines within the WKY and SHR lineages differed in more than 20–30% of the genome. In addition, we found that their genomic regions tagged by the small numbers of polymorphic SNPs were highly enriched for ASDs candidate genes and pathways involved in brain development and neuronal functions [12]. Although SNP-based analyses can only estimate the possible divergent genomic regions, and cannot reveal the actual causal genetic variants, our analysis suggests that there could be potential differences in genes related to ASDs, thus affecting brain functioning and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Although SNP-based analyses can only estimate the possible divergent genomic regions, and cannot reveal the actual causal genetic variants, our analysis suggests that there could be potential differences in genes related to ASDs, thus affecting brain functioning and behavior. Indeed, re-sequencing verified that two known risk genes for ASDs and ADHD in the estimated regions,SLC9A9 and SLC6A3, harbor genetic variants that could be functional [12]. Unfortunately, these two substrains have been used interchangeably in previous research and almost no study, except one examining stress-response[13], has directly compared the two.…”
Section: Introductionmentioning
confidence: 99%